A longitudinal study assessing childcare services' adoption of obesity prevention policies and practices. (31st May 2016) - Yoong, Sze Lin; Finch, Meghan; Nathan, Nicole; Wiggers, John; Lecathelinais, Christophe; Jones, Jannah; Dodds, Pennie; Wolfenden, Luke
Abstract : Aim: Despite ongoing investments to improve the obesogenic environments of childcare settings, little is known regarding how these services have changed their physical activity and nutrition‐promoting practices. This study aims to describe changes in the proportion of Australian childcare services that have adopted best‐practice healthy eating and physical activity practices between 2006 and 2013 and to assess whether adoption varied by socio‐economic status and locality. Methods: A randomly selected sample of nominated supervisors ( n =  358) from childcare services located in New South Wales, Australia, participated in a telephone survey in 2006, 2009, 2010 and 2013. Supervisors reported on their service's adoption of six practices: (i) having written nutrition and physical activity policies; (ii) staff trained in physical activity and nutrition in the past year; (iii) scheduled time for fundamental movement skills and (iv) outdoor play; (v) weekly or less screen time opportunities; and (vi) serving only non‐sweetened beverages. Results: A significant increase in the prevalence of services adopting all but one practice, between 2006 and 2013 was identified. Ninety one percent of services adopted four or more practices, a significant increase from 38% in 2006. There were no differences in the proportion of services adopting each practice by locality and socio‐economic status. Conclusions: Government investment in obesity prevention programmes can equitably improve childcare service's adoption of healthy eating and physical activity promoting practices on a jurisdiction‐wide basis. The establishment of a routine system to monitor adoption of a broader range of practices by childcare services is warranted.